2020
DOI: 10.3390/plants9040436
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local Habitat and Microclimate on the Levels of Secondary Metabolites in Slovak Bilberry (Vaccinium myrtillus L.) Fruits

Abstract: The berries of Vaccinium myrtillus L. are usually collected in the wild for the purpose of being a food source. They are naturally high in phenolic compounds, which possess antioxidative properties, so the berries are therefore often labeled as “functional foods”. This study evaluated seven samples of bilberry fruits from different locations in Slovakia for the content of the main phenolic compounds (anthocyanins, flavonoids and tannins) using European Pharmacopoeia 9 spectrophotometric methods. A thorough ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…Some growth traits ( e.g . plant age) are expected to stimulate accumulation of particular flavonoid compounds (Julkunen‐Tiitto et al 1996; Zou et al 2019; Vaneková et al 2020), while the role of whole plant growth on phenolic metabolism has been discussed in terms of the carbon–nutrient balance hypothesis (Jones & Hartley 1999; Hamilton et al 2001; Strissel et al 2005). The intensity of plant–plant interactions (also as an expression of competition) has been proved to be a key factor, in principle, for metabolic compounds in shrubs (García‐Cervigón et al 2013; Anadon‐Rosell et al 2016; Casolo et al 2020) and, in general, in woody plants (Olano et al 2006), but specific quantification of the effects on flavonoids has been less investigated (Treutter 2005; Weston & Mathesius 2013; Rockenbach & Rizzardi 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some growth traits ( e.g . plant age) are expected to stimulate accumulation of particular flavonoid compounds (Julkunen‐Tiitto et al 1996; Zou et al 2019; Vaneková et al 2020), while the role of whole plant growth on phenolic metabolism has been discussed in terms of the carbon–nutrient balance hypothesis (Jones & Hartley 1999; Hamilton et al 2001; Strissel et al 2005). The intensity of plant–plant interactions (also as an expression of competition) has been proved to be a key factor, in principle, for metabolic compounds in shrubs (García‐Cervigón et al 2013; Anadon‐Rosell et al 2016; Casolo et al 2020) and, in general, in woody plants (Olano et al 2006), but specific quantification of the effects on flavonoids has been less investigated (Treutter 2005; Weston & Mathesius 2013; Rockenbach & Rizzardi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of abiotic factors ( e.g. latitude, soil features) on flavonoid composition of V. myrtillus has been demonstrated (Lätti et al 2008; Rieger et al 2008; Vaneková et al 2020), little is known about the effects of growth traits and plant interactions with changing elevation. Growth traits, such as annual growth and growth rings, have already been used to trace year‐to‐year variations in temperatures (Bär et al 2008; Myers‐Smith et al 2015) or other environmental factors (Rixen et al 2004; Wipf et al 2006; Anadon‐Rosell et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Especially for laboratories that do not have the HPLC analysis capability, the colorimetric technique offers a simple and economical method for anthocyanin determination [ 27 ]. For bilberry and bilberry pomace, similarly to many other fruits, anthocyanin and other secondary metabolite contents largely depend on multiple environmental factors, especially sunlight exposure, altitude, habitat type, and soil carbon content [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result of Mazur et al (2014) indicated that photoperiodic mechanisms, rather than the received light energy per day, caused the observed differences. In another study on black currants, accumulation of anthocyanins and flavonols increased under natural LD conditions, while under identical light energy conditions, photoperiod had little or no effect on the concentration of phenolic compounds (Woznicki et al, 2016). The levels of delphinidin, peonidin, and petudinin type anthocyanins were higher in bilberries grown under 24 h of light compared with 12 h (Uleberg et al, 2012).…”
Section: Arctic Light and Crop Qualitymentioning
confidence: 93%